What defines dry skin? Correlating a range of skin hydration parameters with In Vivo Confocal Raman Spectroscopy - Crowther, Jonathan M.; Matts, Paul J. (International journal of cosmetic science, 2024)
Objective While there are a wide range of approaches for the assessment of skin hydration, it is not always clear how data from them relate to one another or to the skin itself. With the development of in vivo Confocal Raman Spectroscopy (ICRS), it has become possible to measure water concentration as a function of protein/depth within the stratum corneum (SC). This article reports a comparison between electrical skin hydration measures/visual/optical grading and water concentration profiles measured using ICRS, to better understand the relationship between these approaches. Methods SC hydration of lower‐leg skin with varying degrees of dryness was assessed using visual grading (live and from digital images), Corneometer®, Visioscan and ICRS. In addition, a custom fingerprint sensor was used to image surface capacitance (as a surrogate of SC hydration), and SC barrier function was assessed using evaporimetry (to measure trans‐epidermal water loss; TEWL). Results Significant correlations were observed between a number of different skin grading/measurement approaches and ICRS data. ICRS hydration profiles also revealed a region near the SC surface with a relatively flat water profile in dry skin subjects. Conclusions The advent of quantitative in vivo analytical techniques such as ICRS, which can be used in a clinical setting, has enabled greater insight into more conventional approaches for assessing skin dryness. While traditional skin grading and biophysical methods for measuring skin hydration have varying degrees of correlation with one another, they also provide comparatively unique information about different regions within the SC. This should enable a more informed approach to product development in the future. Résumé Objectif Bien qu’il existe un large éventail d’approches pour évaluer l’hydratation de la peau, la façon dont les données qui en résultent sont liées les unes aux autres ou à la peau elle‐même n’est pas toujours claire. Avec le développement de la spectroscopie Raman confocale in vivo (ICRS), il est devenu possible de mesurer la concentration en eau en fonction du rapport protéine/profondeur au sein de la couche cornée (stratum corneum, SC). Cet article rapporte une comparaison entre les mesures électriques ou la classification visuelle/optique de l’hydratation de la peau et les profils de concentration en eau mesurés à l’aide de l’ICRS, afin de mieux comprendre la relation entre ces approches. Méthodes L’hydratation du SC de la peau de la partie inférieure de la jambe avec différents degrés de sécheresse a été évaluée à l’aide d’une classification visuelle (en direct et à partir d’images numériques), du Corneometer®, du Visioscan et de l’ICRS. En outre, un capteur d’empreintes digitales personnalisé a été utilisé pour visualiser la capacité de surface (en tant que substitut de l’hydratation du SC) et la fonction de barrière du SC a été évaluée par évaporimétrie (pour mesurer la perte d’eau transépidermique ; trans‐epidermal water loss, TEWL). Résultats Des corrélations significatives ont été observées entre un certain nombre d’approches différentes de classification/mesure de la peau et les données ICRS. Les profils d’hydratation de l’ICRS ont également révélé une région près de la surface du SC ayant un profil d’eau relativement plat chez les sujets atteints de sécheresse cutanée. Conclusions L’avènement de techniques d’analyse in vivo quantitatives telles que l’ICRS, qui peut être utilisée dans un contexte clinique, a permis de mieux comprendre les approches plus conventionnelles d’évaluation de la sécheresse cutanée. Bien que les méthodes traditionnelles de classification de la peau et les méthodes biophysiques de mesure de l’hydratation de la peau présentent des degrés de corrélation variables entre elles, elles fournissent également des informations comparativement uniques sur différentes régions au sein du SC. Cela devrait permettre une approche plus éclairée du développement de produits à l’avenir. While a wide range of approaches for the assessment of skin hydration exist, it is not always clear how these relate to one another or to the skin itself. This article compares electrical skin hydration measures/visual/optical grading and water concentration profiles measured using in vivo Confocal Raman Spectroscopy, to better understand these relationships.